Alpha glucosidase inhibitory properties of a few bioactive compounds isolated from black rice bran: combined in vitro and in silico evidence supporting the antidiabetic effect of black rice. Issue 35 (12th August 2022) - Bhuyan, Pranjal; Ganguly, Mausumi; Baruah, Indrani; Borgohain, Gargi; Hazarika, Jnyandeep; Sarma, Shruti
Abstract : Alpha glucosidase inhibitors reduce post prandial hyperglycemia and are the drugs of choice for the treatment of type 2 diabetes. As synthetic α-glucosidase inhibitors often produce undesirable side effects, less toxic inhibitors from natural sources are in high demand. Abstract : In view of the recent reports of the antidiabetic effect of the black rice bran extract, an attempt has been made in the present work to evaluate the potential α-glucosidase inhibitory activity of a few selected bioactive compounds present in the pericarp of the black rice. Out of the six bioactive compounds from black rice bran selected for the study, two compounds viz. cyanidin-3-glucoside and 6′- O -feruloylsucrose were identified as novel and highly potent α-glucosidase inhibitors via their in vitro and in silico screenings. The enzyme inhibition assay was corroborated by molecular docking and molecular dynamics simulation studies. Molecular docking studies suggested high binding energies and good binding interactions of these compounds with the active site residues of the receptor protein. A good agreement was found between the results of both modes of evaluation. The experimental results proved that the black rice bran extract can show 62% of alpha glucosidase inhibiting enzyme activity as compared to that of the popular drug Acarbose. While both the docking scores and binding affinity values indicate the formation of a ligand–enzyme complex by the major components of the extract, the molecular dynamics study further indicates the stability of the complex. The pharmacokinetic (ADMET properties) studies of these active compounds also support their use as safe oral anti-diabetic drugs. Thus, the results obtained from these studies of alpha glucosidase inhibition by bioactive compounds present in black rice bran indicate that these bioactive compounds can produce significant antidiabetic activity by inhibiting the active site of the target enzyme and hence these compounds can be used as leads for the synthesis of new antidiabetic drugs.